2021
DOI: 10.21037/atm-20-8165
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of Yizhi Tongmai decoction in the treatment of vascular dementia through network pharmacology and molecular docking

Abstract: Background: Vascular dementia (VaD) is a degenerative cerebrovascular disease that leads to progressive decline of patients' cognitive ability and memory. Yizhi Tongmai (YZTM) decoction is an empirical prescription first formulated by Professor Guomin Si. Our previous experiments proved the effectiveness of this prescription in the treatment of VaD. In this study, we aimed to use network pharmacology and molecular docking technology to systematically explain the potential anti-VaD mechanism of YZTM.Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…And BC, CC, DC, EC, LAC, NC should be greater than or equal to the median value. 14 Functional Enrichment Analyses R software, a free software environment for statistical computing and graphics, was used to perform GO and KEGG functional enrichment analyses for the key targets.…”
Section: Construction Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…And BC, CC, DC, EC, LAC, NC should be greater than or equal to the median value. 14 Functional Enrichment Analyses R software, a free software environment for statistical computing and graphics, was used to perform GO and KEGG functional enrichment analyses for the key targets.…”
Section: Construction Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 99%
“…13 With the development of computer technology and theory of system biology theory, network pharmacology is an emerging interdisciplinary subject, which has great advantages in interpreting the pharmacologic mechanisms of TCM with multiple components, targets and pathways, and is extremely commensurate with the holistic philosophy of TCM. [14][15][16] By network pharmacological analysis, Liu et al found 28 compounds and 421 targets in Huaihua-San formed the main pathways linked to ulcerative colitis, which revealed the mechanism of Huaihua-San against ulcerative colitis. 17 Similarly, with the help of network pharmacology, we predicted and verified the potential pharmacological mechanism of Bu-Yang herbs for postmenopausal osteoporosis via regulating the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the holism concept of TCM, Chinese medicinal formulas are usually treated diseases through several components and targets rather than a single one [ 13 ]. Network pharmacology can abstract the interaction relationship of drugs and targets into a network model and study them via a holistic perspective, consistent with the concept of holism in TCM [ 14 ]. In recent years, it has been recognized as an efficient method to study TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [10] also have found that LDP has a practical therapeutic effect on diabetic nephropathy. A meta-analysis including 14 RCT studies and 918 study participants has reported that LDP categorized formulas are safe and effective in treating DN proteinuria [11]. However, because of the characteristics of multi-compound and multi-target, exploring the underlying molecular mechanism of traditional Chinese medicine (TCM) through cellular or animal studies is relatively tricky [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the holism concept of TCM, Chinese medicinal formulas are usually treated diseases through several components and targets rather than a single one [13]. Network Pharmacology can abstract the interaction relationship of drugs and targets into a network model and study them via a holistic perspective, consistent with the concept of holism in TCM [14]. In recent years, it has been recognized as an e cient method to study TCM.…”
Section: Introductionmentioning
confidence: 99%